Sing and do not stray: male rufous-and-white wrens use duets and physical behaviours to guard their mates. (September 2018) - Kahn, Zachary A.; Moser-Purdy, Christopher; Mennill, Daniel J.
Abstract : In diverse animal taxa, breeding partners coordinate their vocalizations to produce vocal duets. One seldom-studied hypothesis for duets is the paternity guarding hypothesis, which states that male animals create duets to advertise their partner's mated status and minimize extrapair mating attempts between their partner and other males. We experimentally tested the paternity guarding hypothesis in rufous-and-white wrens, Thryophilus rufalbus, a neotropical duetting songbird. We designed a two-part playback experiment: males first experienced a simulated territorial intrusion by a rival male, and were then given opportunities to answer their female breeding partner's songs to create duets. We repeated this experiment during the female's fertile and nonfertile breeding stages. In support of predictions of the paternity guarding hypothesis, male wrens created more duets with their partner's songs during the fertile period compared to the nonfertile period. Additionally, male wrens appeared to physically guard their mates with greater intensity during the fertile period but did not increase their overall song rates, demonstrating that increased duetting rates during the fertile period were a result of a change in male duetting behaviour, rather than a change in song rate. Our study is among the first to experimentally test the paternity guarding hypothesis for duet function, and suggests that male rufous-and-white wrens use both vocal and physical behaviours to guard their paternity. Highlights: Socially monogamous animals may use vocal duets as a paternity guarding strategy. We used playback to study duets and paternity guarding in a tropical songbird. Males created more duets with their breeding partners when they were fertile. Males also appeared to physically guard their mates during the fertile period. Therefore, these tropical birds use vocal and physical behaviours to guard their mates.